Patterns of the Agricultural Income and Impact of Structural Changes Post-Enlargement Among EU States - Mirela-Adriana Rusali (CES Working Papers, 2015)
The article presents the results of analysis on the pattern of agricultural income structure and changes in EU Member States related to the enlargement impact, highlighting gaps and major contributions. While marked differences appear between the EU-15 and post 2004 acceded countries, the major contribution of the Romanian agriculture to the EU economy and the proportion of employment in agriculture, are indicators of a divergent sector development. With a substantial contribution to the UAA, i.e. the 7.9% share in arable land places Romania among the first 6 countries, while the 8.3% share in the area of permanent pasture reveal a potential advantage for livestock grazing. Nevertheless agriculture remaining the foremost source of income for rural households in Romania, its importance has been evidenced a decreasing trend in the post-accession period of time 2007-2013, by comparing to the previous period of time 2001-2006.
Keywords: Q17; Q12; F15; 330; agricultural income; structural changes; post-enlargement; Romania